Introduction : Families in mobility and diasporas in the development processes - (:unkn) unknown (My University, 2019)
Migration, as a specific form of mobility, has shaped public policy in both the South and the North in recent years. Reinforced by the tragedies in the Mediterranean, the 'migration issue' has been framed in the media and politics as a threat to Fortress Europe, despite the fact that African migration to the West is statistically low and essentially intra-continental (Lessault and Beauchemin 2009; Eyebiyi & Mendy2019a). This chapter shows that the triptych of migration, mobility and development goes beyond the simple question of movement and border management and sheds light on migrants' family strategies. These play a role in regulating the spaces of departure, transit and arrival, the routes taken and the symbolic, cultural and political resources generated.
Keywords: African Research